Ototoxicity of Long‐Term α‐Difluoromethylornithine for Skin Cancer Prevention. (27th May 2022) - Chow, Cynthia L.; Havighurst, Thomas; Lozar, Taja; Jones, Todd D.; Kim, KyungMann; Bailey, Howard H.
Abstract : Objective: Evaluate the effects of α‐difluoromethylornithine (DFMO) on hearing thresholds as part of a randomized, double‐blind, placebo‐controlled trial. Methods: Subjects were randomized and assigned to the control (placebo) or experimental (DFMO) group. DFMO or placebo were administered orally (500 mg/m 2 /day) for up to 5 years. Results: Subjects taking DFMO had, on average, increased hearing thresholds from baseline across the frequency range compared to subjects in the control group. Statistical analysis revealed this was significant in the lower frequency range. Conclusions: This randomized controlled trial revealed the presence of increased hearing thresholds associated with long‐term DFMO use. As a whole, DFMO may help prevent and treat certain types of cancers; however, it can result in some degree of hearing loss even when administered at low doses. This study further highlights the importance of closely monitoring hearing thresholds in subjects taking DFMO. Laryngoscope, 133:676–682, 2023